Organic carbon dynamics in interrows of Vitis vinifera with different years of soil use and management (Research, Society and Development, 2021)
This study aimed to evaluate the effects of soil use and management on organic carbon stocks in the interrows of Vitis vinifera with different years of cultivation. A vineyard located in Rio Grande do Sul state, with 4, 9 and 16 years of management, was evaluated. Soil samples from different layers, 0.0-0.10, 0.10-0.20, 0.20-0.30, 0.30-0.40, 0.40-0.50 and 0.50-0.60 m, were collected on wheel tracks, between wheel tracks and under the planting rows. As a reference, samples were collected in native grassland of the region. Organic matter content, bulk density and soil porosity were evaluated. Carbon stock was determined according to the correction of the sampled thickness. The results were subjected to analysis of variance and means were compared by Tukey test at 0.05 probability level. Soil management caused alterations in its structure and organic matter content, observed mainly in the first 30 cm, regardless of the area studied. Highest values of bulk density were observed on the tractor wheel tracks, followed by under the planting row and between wheel tracks. Alteration in soil cover for vineyard planting led to a reduction in the carbon stock, compared to the native grassland. The area under management for 4 years showed higher carbon stocks between the wheel tracks, whereas the areas under 9 and 16 years of management showed highest values in the wheel tracks.